TANTANGAN DAKWAH PADA GENERASI MILENIAL DAN GEN Z: PENDEKATAN BARU DI ERA MODERN - Maulana Wahyu Hidayat; Miftachul Aula; Bustanul Arifin (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The advancement of digital technology has brought significant changes to communication patterns and information dissemination, including Islamic da'wah activities. Millennials and Generation Z, who grew up in a fast-paced and digitally driven environment, demonstrate characteristics, learning styles, and media preferences that differ from previous generations. This study aims to examine the challenges of da'wah among these two generations and formulate relevant approaches in the modern era. Using a qualitative, literature-based research method, the data were obtained from various sources such as scholarly books, national and international journals, academic articles, and official documents discussing digital-based da'wah activities and the interaction between preachers and millennial and Gen Z audiences. The findings indicate that the main challenges of da'wah include shifts in religious behavior, the dominance of social media use, the superficialization of religious knowledge, and changes in communication patterns that demand more flexible and persuasive approaches. In addition, the phenomena of da'wah commodification and spiritual identity crises influence how young generations understand Islamic teachings. This study concludes that da'wah must transform through the utilization of digital technology, the strengthening of religious literacy, and more adaptive communicative approaches so that Islamic messages can be effectively delivered to Millennials and Generation Z.